Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery

By introducing secondary particle structure, graphene conductive framework and carbon coating into the lithium iron phosphate positive electrode material, and doping doped elements, the insufficient performance of existing materials in the field of high-ratio and high-current is solved, and higher rate performance and electrochemical performance are achieved.

CN119812316APending Publication Date: 2025-04-11HUNAN CHANGYUAN LICO NEW ENERGY CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510188236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing rate-type LiFePO4 positive electrode materials show problems such as low conductivity, low lithium ion mobility, poor low temperature, and poor high rate charge and discharge performance in the field of high-speed and high-speed current.

Method used

A lithium iron phosphate positive electrode material is used, which has a secondary particle structure, an internal graphene conductive framework and an external carbon coating. It is doped or co-doped at different element sites of LiFePO4 by doping elements such as aluminum, manganese, vanadium, etc. to increase the lattice defect and improve the diffusion rate and conductivity of lithium ions.

Benefits of technology

By improving the electron transport capability of the material and the diffusion rate of lithium ions, the powder resistance of the material is significantly reduced, the rate performance and electrochemical performance are improved, and the cycle stability and safety of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812316A_ABST
    Figure CN119812316A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate, a lithium ion battery and electric equipment, and relates to the technical field of new energy. The lithium iron phosphate positive electrode material disclosed by the invention has a unique secondary particle structure, a graphene conductive skeleton and a carbon coating layer, so that the powder resistance of particles can be greatly reduced, electron transmission in the material is facilitated, and the polarization effect is reduced. According to the preparation method of the lithium iron phosphate positive electrode material, two-fluid spray drying is adopted, graphene sheets already exist in spray solid spheres after spray drying, then carbon coating and nitrogen protection sintering are performed, and spherical lithium iron phosphate secondary particles with a graphene conductive framework and a carbon coating layer are obtained. Compared with the conventional lithium iron phosphate preparation method comprising a crushing step, the lithium iron phosphate preparation method has the advantages that the damage to the carbon coating layer in the crushing process is avoided, and the rate capability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] With the increasing number of high-power consumption application scenarios in civil, military and industrial fields, such as the application of high-rate load products such as starting batteries, forklift batteries, AGV power batteries, medical equipment, electric scooters, etc., the market's requirements for high-rate discharge of lithium batteries without reducing cycle stability have also increased. At present, the battery cells used in the field of high-rate and high-current are mainly ternary lithium batteries, which are expensive and have poor safety. Olivine-structured lithium iron phosphate (LiFePO4) has become a research hotspot for replacing ternary materials due to its stable discharge voltage, stable structure, good safety performance, long cycle life, rich raw material sources, and no pollution to the environment, in order to achieve the effect of improving safety. At present, there are some shortcomings in the synthesis and practical application of rate-type LiFePO4 positive electrode materials, such as: low conductivity, low lithium ion mobility, poor low temperature resistance, and poor high-rate charge and discharge performance. Summary of the invention

[0003] The purpose of the present application is to provide a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a lithium ion battery, aiming to solve the existing problems.

[0004] To achieve the above objectives, the present application provides a lithium iron phosphate positive electrode material, wherein the lithium iron phosphate positive electrode material has secondary particles.

[0005] There is a graphene conductive skeleton inside the lithium iron phosphate positive electrode material.

[0006] A carbon coating layer is provided on the surface of the lithium iron phosphate positive electrode material.

[0007] In some embodiments, the lithium iron phosphate positive electrode material includes a doping element.

[0008] Wherein, the doping element includes at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably includes aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably includes aluminum and manganese, aluminum and vanadium;

[0009] Preferably, the content of the doping element in the lithium iron phosphate positive electrode material is 100 to 10000 ppm, preferably 2000 to 5000 ppm.

[0010] In some embodiments, the doping amount of the graphene is 0.1% to 2.5% by mass of the iron phosphate, preferably 0.1% to 0.5%;

[0011] Preferably, the mass percentage of the carbon coating layer in the lithium iron phosphate positive electrode material is 1.1 to 3.2%, preferably 1.1 to 2.7%;

[0012] Preferably, the powder resistance of the lithium iron phosphate positive electrode material is ≤10Ω·cm, preferably ≤8.8Ω·cm, and more preferably ≤8.4Ω·cm.

[0013] In some embodiments, the specific surface area of ​​the lithium iron phosphate positive electrode material is 8 to 18 m 2 / g, preferably 10 to 13 m 2 / g;

[0014] Preferably, the particle size D50 of the lithium iron phosphate positive electrode material is 4 to 20 μm, preferably 6 to 14 μm;

[0015] Preferably, the compaction density of the lithium iron phosphate positive electrode material is 2.0 to 2.5 g / cc, preferably 2.15 to 2.35 g / cc;

[0016] Preferably, the 10C discharge specific capacity of the lithium iron phosphate positive electrode material at 25° C. is 115 to 135 mAh / g, preferably 117 to 131 mAh / g, and more preferably 122 to 131 mAh / g.

[0017] The present application also provides a method for preparing a lithium iron phosphate positive electrode material, comprising:

[0018] (1) mixing iron phosphate, a lithium source, a dopant, graphene and a dispersant to obtain a mixed material;

[0019] (2) grinding the mixed material to obtain a slurry;

[0020] (3) subjecting the slurry to two-fluid spray drying to obtain a dry powder;

[0021] (4) The dry powder is mixed with a carbon source and then sintered to obtain a lithium iron phosphate positive electrode material.

[0022] In some embodiments, the molar ratio of the iron ions in the iron phosphate to the lithium ions in the lithium source is 1:(0.95-1.1);

[0023] Preferably, the mass ratio of the iron phosphate to the carbon source, the graphene, and the dopant is 1: (0.05-0.15): (0.001-0.025): (0.001-0.05), preferably 1: (0.08-0.15): (0.001-0.005): (0.001-0.02);

[0024] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium monohydrogen phosphate, and lithium dihydrogen phosphate, preferably lithium carbonate or lithium hydroxide;

[0025] Preferably, the carbon source comprises at least one of glucose monohydrate, glucose, polyethylene glycol, fructose, sucrose, starch, maltose, polyvinyl pyrrolidone, polyvinylidene fluoride, and urea-formaldehyde resin;

[0026] Preferably, the dispersant is pure water, and the solid content of the slurry is adjusted to 20-60%, preferably 30-50%;

[0027] Preferably, the dopant is an oxide, carbonate or ammonium salt of at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably an oxide, carbonate or ammonium salt of aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably an oxide, carbonate or ammonium salt of aluminum and manganese, and an oxide, carbonate or ammonium salt of aluminum and vanadium.

[0028] In some embodiments, a phosphorus source and an iron source having equal molar equivalents of phosphorus and iron are used to replace the iron phosphate, the phosphorus source includes at least one of phosphoric acid, lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate, and the iron source includes at least one of ferrous oxide, ferric oxide, ferrous oxide, ferrous oxalate, and ferric acetate.

[0029] In some embodiments, the particle size D50 of the slurry is 200 to 600 nm, preferably 300 to 500 nm;

[0030] Preferably, the particle size D50 of the dry powder is 4 to 20 μm, preferably 7 to 16 μm;

[0031] Preferably, the air inlet temperature of the two-fluid spray drying is 200-300°C, and the air outlet temperature is 80-120°C;

[0032] Preferably, the sintering temperature is 650-860° C., preferably 700-800° C., and the sintering time is 6-15 hours, preferably 8-10 hours.

[0033] The present application also provides a positive electrode plate, comprising the above-mentioned lithium iron phosphate positive electrode material, or comprising the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method.

[0034] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0035] Compared with the prior art, the beneficial effects of this application include:

[0036] The lithium iron phosphate positive electrode material provided by the present application has a unique lithium iron phosphate secondary particle structure, an internal graphene conductive skeleton, and an external carbon coating layer. Compared with conventional spherical lithium iron phosphate, it can be beneficial to the electron transmission inside the material particles, greatly reduce the powder resistance of the particles, reduce the polarization effect, and thus improve the rate performance of the material. On the basis of the secondary particle morphology of the lithium iron phosphate positive electrode material combined with the graphene conductive skeleton and the carbon coating layer, further doping or co-doping of specific elements at different element sites of LiFePO4 can increase the lattice defects of LiFePO4, help to improve the diffusion rate of lithium ions and the conductivity of primary particles, further reduce the powder resistance of the material, give play to the composite synergistic effect of morphological characteristics and conductive skeleton and carbon coating layer and element doping, and comprehensively improve its electrochemical performance.

[0037] In the preparation method of the lithium iron phosphate positive electrode material of the present application, two-fluid spray drying is used to prepare a powder with a secondary particle morphology. After spray drying, the graphene sheets are present inside the solid secondary particles, and then carbon coating and nitrogen protection sintering are performed. Without the crushing step, spherical lithium iron phosphate secondary particles with a graphene conductive skeleton and a carbon coating layer are obtained. Compared with the conventional lithium iron phosphate preparation method including a crushing step, the process flow of the present application is shorter, and at the same time, the damage to the carbon coating layer during the crushing process is avoided, the rate performance of the material is improved, and the internal resistance of the material is reduced.

[0038] The positive electrode plate and lithium-ion battery provided by the present application have excellent electrochemical performance and high rate capability due to the use of the lithium iron phosphate positive electrode material with low powder resistance of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0040] Figure 1 A schematic diagram of a process for preparing a lithium iron phosphate positive electrode material of the present application;

[0041] Figure 2 A bottom view of a two-fluid nozzle used in the present application;

[0042] Figure 3 This is a SEM image of the lithium iron phosphate positive electrode material of Example 1 magnified 5k times;

[0043] Figure 4 This is a SEM image of the lithium iron phosphate positive electrode material of Example 1 magnified 50k times;

[0044] Figure 5This is a cross-sectional SEM image of the lithium iron phosphate positive electrode material of Example 1. DETAILED DESCRIPTION

[0045] As used herein, the term "prepared from" is synonymous with "comprising". As used herein, the terms "comprising", "including", "having", "containing" or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0046] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0047] In these examples, parts and percentages are by mass unless otherwise indicated.

[0048] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0049] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0050] The present application provides a lithium iron phosphate positive electrode material, wherein the lithium iron phosphate positive electrode material has secondary particles, a graphene conductive skeleton is provided inside the lithium iron phosphate positive electrode material, and a carbon coating layer is provided on the surface of the lithium iron phosphate positive electrode material.

[0051] The lithium iron phosphate positive electrode material provided in the present application, compared with conventional spherical lithium iron phosphate, can facilitate electron transmission inside the material particles, greatly reduce the powder resistance of the particles, reduce the polarization effect, and thus improve the rate performance of the material.

[0052] In some embodiments, the lithium iron phosphate positive electrode material includes a doping element.

[0053] The doping element includes at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably includes aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably includes aluminum and manganese, or aluminum and vanadium.

[0054] On the basis of the secondary particle morphology of lithium iron phosphate positive electrode material combined with graphene conductive skeleton and carbon coating layer, further doping or co-doping of specific elements at different element sites of LiFePO4 can increase the lattice defects of LiFePO4, help to improve the diffusion rate of lithium ions and the conductivity of primary particles, further reduce the powder resistance of the material, give play to the composite synergistic effect of morphological characteristics and conductive skeleton and carbon coating layer with element doping, and comprehensively improve its electrochemical performance.

[0055] The ionic radius of aluminum is small and it is easy to be doped into the Li site of LiFePO4, which can increase the hole mobility of lithium iron phosphate and promote the transformation from intrinsic n-type semiconductor to external p-type semiconductor, thereby improving the electrical conductivity and further improving the electrochemical properties of LiFePO4.

[0056] The ionic radius of manganese and vanadium elements is close to that of iron, and they are easily doped at the Fe site of LiFePO4. The weakening effect of Fe-site doping on the lithium-O bond will increase the lattice volume, obtain higher ion mobility and diffusion coefficient, and reduce the size of primary particles, thereby improving the electrochemical performance of LiFePO4.

[0057] By co-doping at different element sites of LiFePO4 at the same time, for example, using manganese and aluminum, or aluminum and vanadium for dual-element doping, the lattice defects of LiFePO4 can be more effectively increased, which helps to improve the diffusion rate of lithium ions and the conductivity of primary particles, reduce the material powder resistance, and improve its electrochemical performance. In the case of using two dopants for dual-element co-doping, the mass ratio between the two dopants can be 0.1-0.9:0.1-0.9, preferably 0.5:0.5.

[0058] Preferably, the content of the doping element in the lithium iron phosphate positive electrode material is 100 to 10000 ppm, for example, it can be 100 ppm, 500 ppm, 1000 ppm, 1200 ppm, 1500 ppm, 1700 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, 5500 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm or any value between 100 and 10000 ppm, preferably 2000 to 5000 ppm.

[0059] In some embodiments, the doping amount of the graphene is 0.1% to 2.5% of the mass of iron phosphate, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5% or any value between 0.1% and 2.5%, preferably 0.1% to 0.5%.

[0060] In some embodiments, the mass percentage of the carbon coating layer in the lithium iron phosphate positive electrode material is 1.1-3.2%, for example, it can be 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 2.0%, 2.5%, 2.8%, 3.0%, 3.2% or any value between 1.1 and 3.2%, preferably 1.1-2.7%.

[0061] Preferably, the powder resistance of the lithium iron phosphate positive electrode material is ≤10Ω·cm, preferably ≤8.8Ω·cm, and more preferably ≤8.4Ω·cm.

[0062] In some embodiments, the specific surface area of ​​the lithium iron phosphate positive electrode material is 8 to 18 m 2 / g, for example, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 18m 2 / g or 8~18m 2 Any value between 10 and 13 m / g is preferred. 2 / g.

[0063] Preferably, the particle size D50 of the lithium iron phosphate positive electrode material is 4 to 20 μm, preferably 6 to 14 μm;

[0064] Preferably, the compaction density of the lithium iron phosphate positive electrode material is 2.0 to 2.5 g / cc, preferably 2.15 to 2.35 g / cc;

[0065] Preferably, the 10C discharge specific capacity of the lithium iron phosphate positive electrode material at 25° C. is 115 to 135 mAh / g, preferably 117 to 131 mAh / g, and more preferably 122 to 131 mAh / g.

[0066] This application also provides a method for preparing a lithium iron phosphate positive electrode material. Figure 1 ,include:

[0067] S100: mixing iron phosphate, a lithium source, a dopant, graphene and a dispersant to obtain a mixed material;

[0068] S200: grinding the mixed material to obtain a slurry;

[0069] S300: performing two-fluid spray drying on the slurry to obtain a dry powder;

[0070] S400: mixing the dry powder with a carbon source, and then sintering to obtain a lithium iron phosphate positive electrode material.

[0071] In the preparation method of the lithium iron phosphate positive electrode material of the present application, two-fluid spray drying is used to prepare a powder with a secondary particle morphology. After spray drying, the graphene sheets are present inside the solid secondary particles, and then carbon coating and nitrogen protection sintering are performed. Without the crushing step, spherical lithium iron phosphate secondary particles with a graphene conductive skeleton and a carbon coating layer are obtained. Compared with the conventional lithium iron phosphate preparation method including a crushing step, the process flow of the present application is shorter, and at the same time, the damage to the carbon coating layer during the crushing process is avoided, the rate performance of the material is improved, and the internal resistance of the material is reduced.

[0072] Graphene is added during the first mixing. Compared with the carbon source, graphene has better conductivity. Graphene has a lamellar structure and is rigid. It can achieve solid-phase contact between multiple particles. It is insoluble in water and not easy to segregate. The graphene exists on the surface of the primary particles inside the lithium iron phosphate secondary particles and can physically connect multiple particles, thereby forming a conductive skeleton inside the secondary particles. The specific surface area of ​​graphene is relatively large, and the bonding force is insufficient. It is not suitable for coating on the outside and is easy to desorb. The carbon coating layer exists on the surface of the secondary particles. Graphene is a lamellar structure with an equivalent diameter of 2 to 5 microns.

[0073] like Figure 2The two-fluid spray drying nozzle shown has a concentric ring structure, the inner ring sprays the slurry, and the outer ring sprays the compressed air. The pressure of the compressed air is controlled to be 0.1-0.5MPa, so as to ensure the spray granulation effect. Various materials can be evenly atomized to obtain a nearly circular dry powder. The dry powder is an agglomerate of tiny particles, and the particle size D50 of the dry powder is 4-20μm, preferably 7-16μm. In this smaller particle size range, the dry powder is a solid ball. Under the action of surface tension, the spray ball is spherical, and various materials in the mixed material are evenly distributed. By sintering the dry powder, the spherical structure will not be basically changed during the sintering process, thereby forming the lithium iron phosphate secondary particles of the present invention, and the graphene is evenly distributed inside the secondary particles. The graphene has a rigid flaky structure, thereby forming a conductive skeleton in the lithium iron phosphate secondary particles.

[0074] In some embodiments, the molar ratio of the iron ions in the ferric phosphate to the lithium ions in the lithium source is 1:(0.95-1.1), for example, it can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1.0, 1:1.1 or any ratio between 1:(0.95-1.1).

[0075] In some embodiments, the mass ratio of the iron phosphate to the carbon source, the graphene, and the dopant is 1: (0.05-0.15): (0.001-0.025): (0.001-0.05), for example, it can be 1: 0.05: 0.01: 0.01, 1: 0.07: 0.02: 0.01, 1: 0.09: 0.005: 0.05, 1: 0.11: 0.001: 0 .01, 1:0.12:0.005:0.01, 1:0.15:0.001:0.01, 1:0.09:0.02:0.05 or any ratio between 1:(0.05-0.15):(0.001-0.025):(0.001-0.05), preferably 1:(0.08-0.15):(0.001-0.005):(0.001-0.02).

[0076] If the amount of carbon source added is lower than this range, the obtained lithium iron phosphate positive electrode material will have poor conductivity and high powder resistance. If it is too low, it will even lead to insufficient reduction reaction and the lithium iron phosphate positive electrode material will produce impurities.

[0077] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium monohydrogen phosphate, and lithium dihydrogen phosphate, preferably lithium carbonate or lithium hydroxide;

[0078] Preferably, the carbon source includes at least one of glucose monohydrate, glucose, polyethylene glycol, fructose, sucrose, starch, maltose, polyvinyl pyrrolidone, polyvinylidene fluoride, and urea-formaldehyde resin.

[0079] In some embodiments, the dispersant is pure water, and the solid content of the slurry is adjusted to 20-60%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value between 20-60%, preferably 30-50%.

[0080] Preferably, the dopant is an oxide, carbonate or ammonium salt of at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably an oxide, carbonate or ammonium salt of aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably an oxide, carbonate or ammonium salt of aluminum and manganese, and an oxide, carbonate or ammonium salt of aluminum and vanadium.

[0081] In some embodiments, a phosphorus source and an iron source having equal molar equivalents of phosphorus and iron are used to replace the iron phosphate, the phosphorus source includes at least one of phosphoric acid, lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate, and the iron source includes at least one of ferrous oxide, ferric oxide, ferrous oxide, ferrous oxalate, and ferric acetate.

[0082] In some embodiments, the particle size D50 of the slurry is 200-600 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm or any value between 200 and 600 nm, preferably 300-500 nm.

[0083] In some embodiments, the particle size D50 of the dry powder is 4 to 20 μm, for example, 4 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 16 μm, 18 μm, 20 μm, preferably 7 to 16 μm.

[0084] The particle size of the slurry is 200-600nm, which is relatively small. After spray drying, it agglomerates to form a dry powder with a larger particle size. When the dry powder is sintered, the particle size will be reduced by about 10%. Therefore, the preferred particle size range of lithium iron phosphate (6-15μm) is slightly smaller than the preferred particle size range of the dry powder (7-16μm).

[0085] In some embodiments, the air inlet temperature of the two-fluid spray drying in step S300 is 200-300° C., for example, 200° C., 250° C., 300° C. or any value between 200° C. and 300° C., and the air outlet temperature is 80-120° C., for example, 80° C., 90° C., 100° C., 110° C., 120° C. or any value between 80° C. and 120° C. The atomization pressure of the two-fluid spray drying equipment is 0.2-0.4 MPa.

[0086] In some embodiments, the sintering temperature in step S400 is 650-860°C, for example, it can be 650°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 860°C or any value between 650 and 860°C, preferably 700 to 800°C, and the sintering time is 6 to 15 hours, preferably 8 to 10 hours.

[0087] In some embodiments, the graphene is purchased from Hefei Haizhou New Material Technology Co., Ltd., model HZ120X. The present invention may also use other graphene as long as the corresponding effect can be achieved.

[0088] The present application also provides a positive electrode plate, comprising the above-mentioned lithium iron phosphate positive electrode material, or comprising the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method.

[0089] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0090] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0091] The positive electrode plate, lithium-ion battery and electrical equipment provided by the present application have excellent electrochemical performance and high rate capability due to the use of the lithium iron phosphate positive electrode material with low powder resistance of the present application.

[0092] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0093] Example 1

[0094] This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes the following steps:

[0095] (1) Mixing iron phosphate, lithium source, dopant, graphene and dispersant in a material tank at a rotation speed of 600 ppm and stirring evenly to obtain a mixed material.

[0096] The molar ratio of iron ions in iron phosphate to lithium ions in the lithium source is 1:1.05; the mass ratio of iron phosphate to graphene and dopant is 1:0.003:0.01;

[0097] The lithium source is lithium carbonate, the doping agent is manganese tetraoxide and aluminum trioxide, the mass ratio of the two is 1:1, the graphene is in the form of graphene dispersion, and the dispersant is pure water. By adding the above dispersant, the solid content of the mixed material is adjusted to 40%.

[0098] (2) The mixed material was cyclically ground using a sand mill at a grinding speed of 1000 rpm until the final particle size D50 was 400 nm to obtain a slurry.

[0099] (3) The slurry was spray dried by two-fluid spray drying equipment to obtain dry powder with a particle size D50 of 10.9 μm. The two-fluid spray drying had an inlet air temperature of 260° C., an outlet air temperature of 100° C., and an atomization pressure of 0.3 MPa.

[0100] The principle of two-fluid spray drying is that the material is delivered by the material pump and sprayed out from the central nozzle, and the outer ring of the nozzle sprays high-pressure air at the same time to atomize the material. The top view of the nozzle is shown in Figure 2 The atomized droplets are quickly dried after contacting with hot air to obtain dry powder after spray drying.

[0101] (4) The dry powder is mixed with a carbon source by a high-speed mixer, wherein the mass ratio of the iron phosphate to the carbon source is 1:0.1, and the carbon source is glucose. Then, the mixture is sent to a sintering furnace protected by nitrogen, first heated to 750°C, then sintered at a constant temperature for 9 hours, and then naturally cooled to room temperature to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0102] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 10.1 μm; the powder resistance is 6.1 Ω·cm, the 10C discharge capacity at 25°C is 131.7 mAh / g, and the specific surface area is 11.2 m 2 / g, and the compacted density at 150MPa is 2.28g / cc.

[0103] The SEM image of the lithium iron phosphate obtained in this embodiment at a magnification of 5k times is as follows: Figure 3 As shown in the figure, it can be seen that the secondary particles are spherical in shape. The SEM image magnified 50k times is shown in Figure 4 As shown, Figure 4 The red frame in the figure is graphene, and it can be seen that a graphene conductive skeleton is formed in the spherical lithium iron phosphate secondary particles. The SEM image of its cross section is shown in Figure 5As shown, it can be seen that it is a solid sphere.

[0104] Example 2

[0105] This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes the following steps:

[0106] (1) mixing iron phosphate, lithium source, dopant, graphene and dispersant in a material tank at a rotation speed of 600 ppm and stirring evenly to obtain a mixed material;

[0107] The molar ratio of iron ions in the iron phosphate to lithium ions in the lithium source is 1:1.1; the mass ratio of iron phosphate to graphene and dopant is 1:0.001:0.001;

[0108] The lithium source is lithium carbonate, the doping agent is manganese tetraoxide and aluminum trioxide, the mass ratio of the two is 1:1, the graphene is in the form of graphene dispersion, and the dispersant is pure water. By adding the above dispersant, the solid content of the mixed material is adjusted to 50%.

[0109] (2) The mixed material was cyclically ground using a sand mill at a grinding speed of 1000 rpm until the final particle size D50 was 500 nm to obtain a slurry.

[0110] (3) The slurry was spray dried by two-fluid spray drying equipment to obtain dry powder with a particle size D50 of 16.0 μm. The two-fluid spray drying had an inlet air temperature of 300° C., an outlet air temperature of 120° C., and an atomization pressure of 0.4 MPa.

[0111] (4) The dry powder is mixed with a carbon source by a high-speed mixer, wherein the mass ratio of the iron phosphate to the carbon source is 1:0.15, and the carbon source is glucose. Then, the mixture is sent to a sintering furnace protected by nitrogen, first heated to 800°C, then sintered at a constant temperature for 8 hours, and then naturally cooled to room temperature to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0112] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 14.1 μm; the powder resistance is 5.1 Ω·cm, the 10C discharge capacity at 25°C is 128.6 mAh / g, and the specific surface area is 10.1 m 2 / g, and the compacted density at 150MPa is 2.35g / cc.

[0113] Example 3

[0114] This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes the following steps:

[0115] (1) mixing iron phosphate, lithium source, dopant, graphene and dispersant in a material tank at a rotation speed of 600 ppm and stirring evenly to obtain a mixed material;

[0116] The molar ratio of iron ions in iron phosphate to lithium ions in the lithium source is 1:0.95; the mass ratio of iron phosphate to graphene and dopant is 1:0.005:0.02;

[0117] The lithium source is lithium carbonate, the doping agent is manganese tetraoxide and aluminum trioxide, the mass ratio of the two is 1:1, the graphene is in the form of graphene dispersion, and the dispersant is pure water. By adding the above dispersant, the solid content of the mixed material is adjusted to 30%.

[0118] (2) The mixed material was cyclically ground using a sand mill at a grinding speed of 1000 rpm until the final particle size D50 was 300 nm to obtain a slurry.

[0119] (3) The slurry was spray dried by two-fluid spray drying equipment to obtain dry powder with a particle size D50 of 7.0 μm. The two-fluid spray drying had an inlet air temperature of 200° C., an outlet air temperature of 80° C., and an atomization pressure of 0.2 MPa.

[0120] (4) The dry powder is mixed with a carbon source by a high-speed mixer, wherein the mass ratio of the iron phosphate to the carbon source is 1:0.08, and the carbon source is glucose. Then, the mixture is sent to a sintering furnace protected by nitrogen, first heated to 700°C, then sintered at a constant temperature for 10 hours, and then cooled naturally to room temperature to obtain lithium iron phosphate with a spherical secondary particle structure having a graphene conductive skeleton and a carbon coating layer.

[0121] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 6.1 μm; the powder resistance is 8.4 Ω·cm, the 10C discharge capacity at 25°C is 127.3 mAh / g, and the specific surface area is 13.0 m 2 / g, and the compacted density at 150MPa is 2.21g / cc.

[0122] Example 4

[0123] On the basis of Example 1, the dopant is changed from manganese tetraoxide and aluminum trioxide to aluminum trioxide and vanadium pentoxide, and the mass ratio of the two is 1:1. Other than this, the same as Example 1 is obtained to obtain lithium iron phosphate with a spherical secondary particle structure having a graphene conductive skeleton and a carbon coating layer.

[0124] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 9.4 μm; the powder resistance is 6.3 Ω·cm, the 10C discharge capacity at 25°C is 130.8 mAh / g, and the specific surface area is 11.6 m2 / g, and the compacted density at 150MPa is 2.26g / cc.

[0125] Example 5

[0126] In step (1) of Example 1, the lithium source is changed from lithium carbonate to lithium hydroxide, and the iron phosphate is changed to ammonium dihydrogen phosphate and ferrous oxalate having equal molar equivalents of phosphorus and iron. Other than this, the same procedures as in Example 1 are performed to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0127] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 11.5 μm; the powder resistance is 7.2 Ω·cm, the 10C discharge capacity at 25°C is 126.8 mAh / g, and the specific surface area is 10.3 m 2 / g, and the compacted density at 150MPa is 2.15g / cc.

[0128] Example 6

[0129] In step (1) of Example 1, the dopant was changed from manganese tetraoxide and aluminum oxide to manganese tetraoxide. Other than this, the same procedures as in Example 1 were performed to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0130] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 10.3 μm; the powder resistance is 7.1 Ω·cm, the 10C discharge capacity at 25°C is 122.1 mAh / g, and the specific surface area is 10.7 m 2 / g, and the compacted density at 150MPa is 2.29g / cc.

[0131] Example 7

[0132] In step (1) of Example 1, no dopant is added. Other than this, the same procedures as in Example 1 are performed to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0133] The particle size D50 of the lithium iron phosphate prepared in this embodiment is 11.0 μm; the powder resistance is 8.8 Ω·cm, the 10C discharge capacity at 25°C is 117.3 mAh / g, and the specific surface area is 11.8 m 2 / g, and the compacted density at 150MPa is 2.31g / cc.

[0134] Comparative Example 1

[0135] In step (1) of Example 1, graphene is not added. Other than this, the same procedures as in Example 1 are followed to obtain lithium iron phosphate having a spherical secondary particle structure with a carbon coating layer.

[0136] The particle size D50 of the lithium iron phosphate prepared in this comparative example is 9.5 μm; the powder resistance is 15.0 Ω·cm, the 10C discharge specific capacity at 25°C is 103.9 mAh / g, and the specific surface area is 11.7 m 2 / g, and the compacted density at 150MPa is 2.33g / cc.

[0137] Comparative Example 2

[0138] In step (4) of Example 1, no carbon source is added, and the dry powder is directly sent to a nitrogen-protected sintering furnace for sintering. Other than this, the same procedures as in Example 1 are performed to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton.

[0139] The particle size D50 of the lithium iron phosphate prepared in this comparative example is 9.9 μm; the powder resistance is 2320.1 Ω·cm, the 10C discharge capacity at 25°C is 90.2 mAh / g, and the specific surface area is 6.9 m 2 / g, and the compacted density at 150MPa is 2.38g / cc.

[0140] Comparative Example 3

[0141] In step (1) of Example 1, the mass ratio of iron phosphate to graphene and dopant is set to 1:0.003:0.1; other than this, the same as Example 1 is performed to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0142] The particle size D50 of the lithium iron phosphate prepared in this comparative example is 9.7 μm; the powder resistance is 8.1 Ω·cm, the 10C discharge specific capacity at 25°C is 116.6 mAh / g, and the specific surface area is 16.2 m 2 / g, and the compacted density at 150MPa is 2.11g / cc.

[0143] Comparative Example 4

[0144] In step (3) of Example 1, the slurry is spray dried by centrifugal spray drying equipment to obtain a dry powder with a particle size D50 of 26.4 μm. The inlet air temperature of the centrifugal spray drying is 260°C, the outlet air temperature is 100°C, and the centrifugal speed is 18000 rpm; otherwise, the same as Example 1 is obtained to obtain lithium iron phosphate having a spherical secondary particle structure with a graphene conductive skeleton and a carbon coating layer.

[0145] The principle of centrifugal spray drying is to use a material pump to transport the slurry through the material delivery pipe to the centrifugal dispersion disk, and the slurry is atomized under the action of the high-speed rotation of the centrifugal dispersion disk. The atomized small droplets are quickly dried after contacting with hot air to obtain dry powder after spray drying.

[0146] It should be noted that, since the particle size of the dry powder prepared by the centrifugal spray drying equipment is too large, hollowness is formed inside the secondary particles during the drying process, that is, the obtained lithium iron phosphate is a hollow spherical secondary particle structure.

[0147] The particle size D50 of the lithium iron phosphate prepared in this comparative example is 21.7 μm; the powder resistance is 15.0 Ω·cm, the 10C discharge specific capacity at 25°C is 112.5 mAh / g, and the specific surface area is 13.6 m 2 / g, and the compacted density at 150MPa is 2.30g / cc.

[0148] The performance testing method of the lithium iron phosphate positive electrode materials prepared in each embodiment and comparative example is as follows.

[0149] (1) Electrochemical test

[0150] The positive electrode material: conductive agent acetylene black: binder PVDF = 90:5:5 is configured into a mixture, and then N-methyl-2-pyrrolidone is added at a solid content of 42.78%, degassed and stirred evenly, coated, dried, rolled, punched, and vacuum dried to prepare the positive electrode plate. The positive electrode plate is assembled into a CR2430 button battery with a Li sheet negative electrode, a polypropylene separator, and a special electrolyte for lithium iron in a vacuum glove box. The test was carried out on the LAND battery test system manufactured by Wuhan Landian Electronics Co., Ltd. The charge and discharge voltage range is 2.0~3.75V. Table 1 shows the discharge capacity of each battery at a rate of 10C at 25°C.

[0151] (2) Compacted density and powder resistance test

[0152] The compaction density and powder resistance at 150MPa were measured using Yuanneng PRCD1100 compaction density & powder resistance meter. The test conditions were pressure relief mode, starting pressure 10MPa, ending pressure 200MPa, step pressure 20MPa, holding time 10s, pressure relief pressure 3MPa, holding time (after pressure relief) 10s, and sample mass 0.98g. Table 1 shows the compaction density and powder resistance data at 150MPa for each sample.

[0153] (3) Particle size test

[0154] The particle size of the lithium iron phosphate positive electrode material was determined using a Malvern 3000 laser particle size analyzer. The test conditions were a particle refractive index of 1.692, an absorbance of 1.0, a dispersant (water) refractive index of 1.330, a circulation rate of 2600r / min, and a light shielding degree of 7%-12%. Weigh an appropriate amount of sample in a beaker, add 20mL of alcohol to disperse and perform ultrasound in an ultrasonic instrument for 30S to obtain a mixed sample. Add 3-5 drops of 5% sodium hexametaphosphate to the injector and test the background. Then add the mixed sample to the injector until the light shielding degree is 7-12%, perform ultrasound inside the particle size analyzer for 20 seconds, and perform a particle size test after stabilization for 5s. Table 1 shows the particle size data of each sample.

[0155] (4) Specific surface area test

[0156] The specific surface area tester BSD-660S manufactured by Bester was used to test the specific surface area of ​​lithium iron phosphate cathode materials. Specifically, the nitrogen output pressure was set to 1.5 bar, the equipment was preheated for 30 minutes, the sample to be tested was added to 2 / 3 of the bulb, vacuum degassed at 200 degrees for two hours, cooled at room temperature for 20 minutes, the filling rod and filter were added, the sample tube was installed on the analyzer, and sufficient liquid nitrogen was added to the Dewar tank. After the vacuum leak detection of the equipment was completed, the automatic test began.

[0157] Table 1 Performance parameters of lithium iron phosphate positive electrode materials of various embodiments and comparative examples

[0158]

[0159] According to Table 1, the powder resistance of the lithium iron phosphate positive electrode material obtained in each embodiment of the technical solution of the present application is ≤10Ω·cm, preferably ≤8.8Ω·cm, more preferably ≤8.4Ω·cm, and the 10C discharge capacity at 25°C is ≥117mAh / g, preferably ≥122mAh / g, which significantly improves the electrochemical performance of the material compared with the comparative example. In addition, the compaction density at 150MPa is 2.15-2.35g / cc, and the specific surface area is 10-13m 2 / g, and the particle size D50 is 6.1-14.1μm, both of which are within the excellent product performance range, achieving significant technical progress and unexpected technical effects.

[0160] According to Table 1, compared with Example 1, Comparative Example 1 does not add graphene, resulting in a significant increase in the powder resistance of the prepared lithium iron phosphate material, and a significant decrease in the 10C discharge capacity at 25°C, which will correspondingly lead to a deterioration in the rate performance of the battery; Comparative Example 2 does not add a carbon source, resulting in a sharp increase in the powder resistance, and a further significant decrease in the 10C discharge capacity at 25°C, resulting in the material being unable to be applied; the amount of dopant used in Comparative Example 3 is too much, exceeding the preferred range of the present invention, resulting in an increase in the specific surface area of ​​the material, and side reactions are prone to occur, resulting in a significant decrease in the 10C discharge capacity at 25°C, which is not conducive to the performance of the material; Comparative Example 4 does not adopt the dual-fluid spray drying process of the present invention but adopts the conventional centrifugal spray drying process, and the particle size of the prepared lithium iron phosphate material is too large and hollow, resulting in a significant increase in the powder resistance of the material, a significant decrease in the discharge capacity, and a deterioration in the rate performance.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0162] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material has secondary particles, There is a graphene conductive skeleton inside the lithium iron phosphate positive electrode material. A carbon coating layer is provided on the surface of the lithium iron phosphate positive electrode material.

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium iron phosphate positive electrode material includes doping elements, Wherein, the doping element includes at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably includes aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably includes aluminum and manganese, aluminum and vanadium; Preferably, the content of the doping element in the lithium iron phosphate positive electrode material is 100 to 10000 ppm, preferably 2000 to 5000 ppm.

3. The lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The doping amount of the graphene is 0.1% to 2.5% of the mass of the iron phosphate, preferably 0.1% to 0.5%; Preferably, the mass percentage of the carbon coating layer in the lithium iron phosphate positive electrode material is 1.1 to 3.2%, preferably 1.1 to 2.7%; Preferably, the powder resistance of the lithium iron phosphate positive electrode material is ≤10Ω·cm, preferably ≤8.8Ω·cm, and more preferably ≤8.4Ω·cm.

4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the lithium iron phosphate positive electrode material is 8 to 18 m 2 / g, preferably 10 to 13 m 2 / g; Preferably, the particle size D50 of the lithium iron phosphate positive electrode material is 4 to 20 μm, preferably 6 to 14 μm; Preferably, the compaction density of the lithium iron phosphate positive electrode material is 2.0 to 2.5 g / cc, preferably 2.15 to 2.35 g / cc; Preferably, the 10C discharge specific capacity of the lithium iron phosphate positive electrode material at 25° C. is 115 to 135 mAh / g, preferably 117 to 131 mAh / g, and more preferably 122 to 131 mAh / g.

5. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: (1) mixing iron phosphate, a lithium source, a dopant, graphene and a dispersant to obtain a mixed material; (2) grinding the mixed material to obtain a slurry; (3) subjecting the slurry to two-fluid spray drying to obtain a dry powder; (4) The dry powder is mixed with a carbon source and then sintered to obtain a lithium iron phosphate positive electrode material.

6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The molar ratio of the iron ions in the iron phosphate to the lithium ions in the lithium source is 1:(0.95-1.1); Preferably, the mass ratio of the iron phosphate to the carbon source, the graphene, and the dopant is 1: (0.05-0.15): (0.001-0.025): (0.001-0.05), preferably 1: (0.08-0.15): (0.001-0.005): (0.001-0.02); Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium monohydrogen phosphate, and lithium dihydrogen phosphate, preferably lithium carbonate or lithium hydroxide; Preferably, the carbon source comprises at least one of glucose monohydrate, glucose, polyethylene glycol, fructose, sucrose, starch, maltose, polyvinyl pyrrolidone, polyvinylidene fluoride, and urea-formaldehyde resin; Preferably, the dispersant is pure water, and the solid content of the slurry is adjusted to 20-60%, preferably 30-50%; Preferably, the dopant is an oxide, carbonate or ammonium salt of at least one of aluminum, manganese, vanadium, niobium, molybdenum, nickel, magnesium and titanium, preferably an oxide, carbonate or ammonium salt of aluminum and at least one of manganese, vanadium, niobium and molybdenum, more preferably an oxide, carbonate or ammonium salt of aluminum and manganese, and an oxide, carbonate or ammonium salt of aluminum and vanadium.

7. The method for preparing the lithium iron phosphate positive electrode material according to claim 5 or 6, characterized in that: A phosphorus source and an iron source having equal molar equivalents of phosphorus and iron are used to replace the iron phosphate, wherein the phosphorus source includes at least one of phosphoric acid, lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate, and the iron source includes at least one of ferrous oxide, ferric oxide, ferrous tetroxide, ferrous oxalate, and ferric acetate.

8. The method for preparing a lithium iron phosphate positive electrode material according to any one of claims 5 to 7, characterized in that: The particle size D50 of the slurry is 200 to 600 nm, preferably 300 to 500 nm; Preferably, the particle size D50 of the dry powder is 4 to 20 μm, preferably 7 to 16 μm; Preferably, the air inlet temperature of the two-fluid spray drying is 200-300°C, and the air outlet temperature is 80-120°C; Preferably, the sintering temperature is 650-860° C., preferably 700-800° C., and the sintering time is 6-15 hours, preferably 8-10 hours.

9. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, or comprises the lithium iron phosphate positive electrode material prepared by the preparation method according to any one of claims 5 to 8.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Lithium iron phosphate positive electrode material with high cycle stability and preparation method of lithium iron phosphate positive electrode material

    CN120998972A

  • A lithium iron phosphate positive electrode material with high cycle stability and a preparation method thereof

    CN120998972B